Solar Tracking System with New Hybrid Control in Energy Production Optimization from Photovoltaic Conversion for Polish Climatic Conditions - Grażyna Frydrychowicz-Jastrzębska; Artur Bugała (Energies, 2021)
This paper presents a comparison of the 24-month production of electricity and momentary power by two photovoltaic systems with a nominal power of 1000 Wp each. The analyzed systems are connected to the power grid and operate independently: a fixed system with optimal all-year-round angular positioning and an astronomical-sensor-controlled dual-axis tracking system. The systems under consideration consist of PV modules with a unit electrical power of 200 Wp, and the production technology of those modules is the same. The tested systems were located on the building rooftop of the Faculty of Control, Robotics and Electrical Engineering of the Poznan University of Technology in Poland (Central Poland, 52°24.4152′ N, 16°55.7958′ E) at a height of 30 m above ground level. The measurements take into account the consumption of electricity by the actuators of the dual-axis positioning system. Increases in the produced electricity by 35.6% and 44.7% were observed for local climatic conditions during the first and second measuring years, respectively, when comparing the use of the dual-axis tracking system with the use of fixed units. Results show that the analyzed region of central Poland, represented by the city of Poznań, creates favorable climatic conditions for the use of astronomical-sensor spatial positioning systems for photovoltaic modules, also in the case of a significant share of diffuse solar radiation in the global value. These results may make the planning of solar tracking investments easier and help with the estimate calculations of the total investment return period and operational costs.